PENGARUH ISLAMIC PROGRESSIVE MUSCLE RELAXATION (IPMR) TERHADAP PENURUNAN KADAR KORTISOL PASIEN PRE OPERASI DI RUANG AZZAHRA 2 RSI JEMURSARI SURABAYA - Zahroh, Chilyatiz; Khamida, Khamida; Rokhman Saleh, Nanang (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2018)
Surgery is a medical action can cause stress on the patient. Stress patient who will undergo surgery must be well managed in order not to harm patients. The purpose of this study was to analyze the influence of Islamic progressive muscle relaxation (IPMR) against the patient's decrease cortisol levels. This research was experimental research with approach of pre-post test design. The population were all patients treated in Azzahra during September 2017, with research samples of 30 respondents obtained via simple random sampling techniques. Independent variables was Islamic progressive muscle relaxation, whereas cortisol levels was dependent variables. The data of Cortisol levels was collected through the patient's blood sample. Data were analyzed with a Wilcoxon signed rank test. Results of the study indicate that there are significant levels of cortisol after patient's IPMR. Cortisol levels in the normal range can modulate the immune system so as to strengthen the body's immune. Nurses can make the effort an effective, easy and cheap to reduce stress to patients who will undergo surgery with technique IPMR. Keywords: Islamic, Progressive, Muscle, Relaxation, Cortisol, Stress